Psychological Training of Future Languages’ Teachers - Nikolaychuk, I. (Psychological Prospects Journal, 2013)
The article deals with languages’ students’ awareness of their future professional training. It looks into the issue of updating specialists’ education by means of special courses, trainings that build up additional skills required for fiction (poetic) text comprehension.